Disease agents affecting the eggs and adults of horseshoe crab, Tachypleus gigas (Muller, 1785) and Carcinoscorpius rotundicauda (Latreille, 1802) in laboratory culture - Eng, Heuh Theng (2012)
This study was conducted to identify different disease agents affecting the development of eggs and adults horseshoe crabs and to determine the effect of aeration on the horseshoe crab eggs development. Tachypleus gigas and Carcinoscorpius rotundicauda eggs used in this study were incubated using a conventional culture system. Samples with signs of infection were examined under a compound microscope and photographed. Eggs inoculations were prepared and cultured on Sabouraud Dextrose salt Agar for fungal isolation and TrypticaseTM Soy Broth (TSB) for bacterial isolation. Identification of different disease agents were conducted based on the morphology of fresh and stained mounts as well as the biochemical characters of the isolated fungi and bacteria. Adults of T. gigas and C. rotundicauda were examined similarly. This study was also conducted to determine the effect of aeration on development of T. gigas eggs. Eggs incubations in water medium were carried out in two treatments; with and without aeration. The eggs of T. gigas were infected with Aspergillus sp. and A. niger, while for C. rotundicauda, the eggs were infected with fungi Aspergillus niger, Penicillium sp. and Gliocladium sp. The eggs of T. gigas were infected with bacterial Corynebacterium sp. and Enterococcus faecalis, while C. rotundicauda eggs were infected with E. faecalis and Shewanella putrefaciens. As for adult C. rotundicauda, E. faecalis and Bacillus cereus were isolated from the prosoma and S. putrefaciens was found in the book gills. A trematode worm, identified as Planaria sp., was found in all parts of the body of adult C. rotundicauda. Percentage of hatching was found to be significantly lower (P<0.05) for T. gigas eggs incubated with aeration as compared with those without aeration.